Called to meet Christ in scripture, church, and sacraments : Christian life education high school series by Ester V. Frago and Josephine C. Dango - Frago, Ester V.; Dango, Josephine C. (Quezon City : Sibs Publishing House, Inc., 2017)
"The new grade 7 book, entitled Called to Celebrate Our Catholic Identity and Mission, aims to respond to the need for young students to understand the basic core of our Catholic faith with the hope of providing them a more solid foundation in appreciating the topics and themes in the succeeding books of the series." These key themes from the core of what we believe, pray, and do as Catholics. They help us understand our identity and by doing so, bring to light our mission as disciples of Jesus. The discussion of these basic tenets of faith culminate, in the celebration of the Sacrament of Confirmation, the sacrament that perfects the grace we received at Baptism and empowers us to live out more faithfully the mission we received as baptized Catholics. The new grade 7 book presents key themes of the Catholic faith that can help deepen the student's appreciation for the old Testament, the life, mission, and Paschal Mystery of Jesus Christ as well as the life of the early Church, and Catholic morality. Also responds to the need to provide religious instruction to students entering junior high school who may not have had formal Catholic religious classes during their elementary grades. By presenting the basic of the Catholic faith, students will have an opportunity to learn these foundational themes before they venture into a more detailed study of the Old and New Testaments, as well as the complex issues related to the Catholic moral teachings. Lastly, the third edition of CLES responds to the signs and needs of the times by including the latest Catholic teachings of Pope Benedict XVI and pope Francis. It provides more examples of authentic and creative assessments and student activities, and it acknowledges the ever-evolving context of the fast-paced and digital world of the youth. This affirms that teaching the Catholic faith, while fundamentally the same at its core, seeks to find new ardor, new methods, and new expression-all of these are characteristics of the New Evangelization"
Includes glossary and bibliography.
English text.
Keywords: Christian education; Religious education